A Multivariate Cointegration Analysis of the Macroeconomic Determinants of Carbon Emissions in Malaysia - Rasiah, Ratneswary; Somasundram, Sotheeswari; Subramaniam, Geetha (International Journal of Energy Economics and Policy, 2018)
Global warming is one of the greatest threats to mankind, as it adversely affects Mother Earth and its ecosystem, human health, the greater economy and is considered a threat to national security. There has been an exponential growth in the number of environmental studies carried out over the past few decades as scholars, climate researchers and governments search for the various factor causing global warming and the feasible solutions to address this potentially catastrophic problem. This paper will contribute further to the existing body of knowledge on the underlying causes of global warming, with the specific aim of investigating the long-run relationships between carbon emissions and its regressors comprising of per capita income, energy use, trade openness, and financial development in Malaysia over the period from 1970 to 2016. The econometric time series analysis of multivariate cointegration is applied in this study to establish the possible causal relations between the variables concerned. The cointegration test and the vector error correction model display evidence of positive long-run relationships between per capita income and carbon emissions, and between trade openness and carbon emissions, while energy use is negatively related to carbon emissions. There is also evidence that the bulk of the variations in the CO2 emissions is attributed to its own variations through further innovation analysis using variance decompositions. The study concludes with an examination of policy implications of the findings. Keywords: Carbon emissions; trade openness; energy; financial development; VECM JEL Classifications: Q39, Q56 DOI: https://doi.org/10.32479/ijeep.7110